Three Years of the the Indigenous Peoples Rights Act: Its Impact on Indigenous Communities - Castro, Nestor T. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2008)
It has been three years since the signing of the Indigenous People's Right Act of 1997. A landmark piece of legislation, it guarantees the rights of IPs to ancestral domain, self-governance and empowerment, social justice and human rights, and cultural integrity.. A petition seeking that the law be declared unconstitutional has been filed with the Supreme Court, arguing among others that the granting of ownership over ancestral domains, which includes all natural resources found thereat, was unconstitutional, since all subsurface mineral resources belong to the State. The National Commission on IPs (NCI P) created by law does not enjoy funding support at all. The changes in administration and consequent new appointments and creation of overlapping bodies have also disrupted its organizational functions. The mining sector resents the need for Free and Prior Informed Consent (FPIC) aside from the already tedious set of permits required by government. So far only two mining companies have secured this consent while several others have abandoned investment plans. Although intended to uplift the quality of life and promote unity among IPs, the IPRA has so far brought more disunity and mistrust than upliftment. The IPRA spawned organizations both for and against it and encouraged corruption especially in the issuance of FPICs. As an ancestral domain law which primarily grants security of tenure to IPs through the issuance of Certificate of Ancestral Domain Titles (CADTs), the IPRA has failed miserably. In three years not a single CADT has been issued, a fact favorable to those with the opinion that the IPs were better off without the IPRA. But while the law has not made good its promises, the IPRA has succeeded in making IPs politically aware of their rights within Philippine society, certainly a positive step towards self-determination.
Keywords: I{RA, Indigenous People' s Rights Act, RA 8371, Assessment